Development of 11 microsatellite loci for an endangered herb, Paraisometrum mileense (Gesneriaceae), in southwest China(1) - Tang, An-Jun (Botanical Society of America, 2013)
• Premise of the study: Microsatellite markers were developed to investigate the genetic diversity and population structure of the endangered species Paraisometrum mileense, as well as its evolutionary history. • Methods and Results: Using the Fast Isolation by AFLP of Sequences COntaining repeats (FIASCO) protocol, 11 polymorphic primer sets were obtained in P. mileense. The number of alleles per locus ranged from one to nine with an average 3.8, and the observed and expected heterozygosities ranged from 0 to 1 and 0 to 0.89, respectively, for the available three populations. • Conclusions: These markers may be useful for further investigation of the conservation genetics of P. mileense.